Plural Loves : Designs for Bi and Poly Living. - Anderlini-D'Onofrio, Serena (Taylor and Francis, 2014)
When limitations are removed from loving (and from lovemaking), new worlds of possibility are opened. This book presents insiders' viewpoints on bisexual/polyamorous living!With historical and theoretical perspectives, testimonials, reports from the field, and creative writing, Plural Loves: Designs for Bi and Poly Living examines group marriage, polyfidelity, cheating, solo-sex (and group solo-sex), utopian communities, tantric expression and sacred eroticism, transculturalization, and much more. This book explores the common ground shared by the bisexual and polyamorist movements.